The case for open science: rare diseases. Issue 3 (11th September 2020) - Rubinstein, Yaffa R; Robinson, Peter N; Gahl, William A; Avillach, Paul; Baynam, Gareth; Cederroth, Helene; Goodwin, Rebecca M; Groft, Stephen C; Hansson, Mats G; Harris, Nomi L; Huser, Vojtech; Mascalzoni, Deborah; et al.
Abstract: The premise of Open Science is that research and medical management will progress faster if data and knowledge are openly shared. The value of Open Science is nowhere more important and appreciated than in the rare disease (RD) community. Research into RDs has been limited by insufficient patient data and resources, a paucity of trained disease experts, and lack of therapeutics, leading to long delays in diagnosis and treatment. These issues can be ameliorated by following the principles and practices of sharing that are intrinsic to Open Science. Here, we describe how the RD community has adopted the core pillars of Open Science, adding new initiatives to promote care and research for RD patients and, ultimately, for all of medicine. We also present recommendations that can advance Open Science more globally.